2017
DOI: 10.18632/oncotarget.20987
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein inhibits progression of osteosarcoma cells through inactivation of the Wnt/β-catenin signaling pathway

Abstract: Osteosarcoma is a very common type of malignant bone tumor in children and young adults and aberrant activation of Wnt/β-catenin signaling pathway has been discovered in osteosarcoma. The traditional Chinese medicine baicalein was proved to have anti-proliferative and anti-metastatic properties in osteosarcoma, but the mechanism remained poorly understood. In the present study, we assessed the effects of baicalein on osteosarcoma and detected the potential molecular mechanism. We found that baicalein significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…The Wnt/β-catenin pathway regulates numerous cellular processes, including cell proliferation, metastasis and differentiation (27,28). Abnormal activation of the Wnt/β-catenin pathway promotes OS development and progression (29). WIF1 serves as a regulator of Wnt/β-catenin signaling (30).…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-catenin pathway regulates numerous cellular processes, including cell proliferation, metastasis and differentiation (27,28). Abnormal activation of the Wnt/β-catenin pathway promotes OS development and progression (29). WIF1 serves as a regulator of Wnt/β-catenin signaling (30).…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein decreases the bone-resorptive activity of osteoclasts and inhibits osteoclast differentiation, subsequently promoting osteoclast apoptosis [17, 52]. Inducing osteoclast apoptosis and cell cycle arrest, baicalein leads to inhibited tumour growth in osteosarcoma cells by inhibiting Wnt/β-catenin pathway [69, 70].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the Wnt signaling pathway serves an essential role in the cancer cell cycle and proliferation ( 12 , 13 ). C-Myc, CCND1, and AXIN2 are well-known target genes of the Wnt signaling pathway ( 14 17 ).…”
Section: Resultsmentioning
confidence: 99%